Performance Comparison of a Sensorless PMBLDC Motor Drive System with Conventional and Fuzzy Logic Controllers. (2016) - Joy, Jino; Ushakumari, S.
Abstract: In this paper, speed control and torque ripple minimization of a sensorless Permanent Magnet Brushless DC (PMBLDC) motor drive system with varying load is analyzed. Constant speed operation with minimum torque ripple during transient state is the most difficult part in the drive system. At starting condition, if the motor is started with constant DC source, the current is too high due to the absence of back EMF. Therefore the motor will start with high torque ripples. In order to eliminate the torque ripples during starting condition by limiting the starting speed of the motor with properly designed speed controller and varying DC source from zero to its rated voltage, this will improve the reliability of PMBLDC motor. Here, the speed control and torque ripple minimization of a sensorless PMBLDC motor during starting and running condition with conventional and fuzzy logic controllers are proposed. The performance parameters of a PMBLDC motor with these controllers are analyzed through MATLAB/Simulink software.